The Relationship Between Job Empowerment and Employee Retention : The Mediating Role of Flow Experience - Mark, Kasa; Zaiton, Hassan; Sheila Lim, Omar Lim; Dayang Kartini, Abang Ibrahim; Wang, Li Cheng (Elsivier Scopus, 2024)
Empowerment fosters responsibility and innovation in achieving organizational objectives. This study investigates the impact of psychological and structural empowerment on employee retention in the hotel industry of Sarawak, with flow experience as a mediating factor. A total of 256 valid questionnaires were collected from the respondents. The data were analysed using the Statistical Package for Social Sciences (SPSS) version 26 PROCESS Model 4 approach and G*Power software to calculate the statistical power to determine the minimum sampling size. The findings show a positive relationship between job empowerment dimensions and employee retention while flow experience acting as a significant mediator. Findings of this study suggest that hotel management should consider job empowerment strategies to enhance employee retention.